2014
DOI: 10.1186/1472-6831-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of QMix™ endodontic irrigating solution on human bone marrow mesenchymal stem cells

Abstract: BackgroundDebridement and disinfection of the root canal system is a crucial step in endodontic procedures. The effectiveness of irrigation relies on both the mechanical flushing action and the ability of irrigants to dissolve tissue and kill bacteria. The objective of the present study is to evaluate and compare the cytotoxicity of QMix™ root canal irrigating solution on immortalized human bone marrow mesenchymal stem cells (hTERT-MSC-C1) and to compare it with that of sodium hypochlorite (NaOCl).MethodsImmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 49 publications
4
27
2
3
Order By: Relevance
“…In the EC group, in which QMix was used for 1 min, the results were similar to those in the group in which QMix was used for 3 min without activation. Although this suggests that the absence of an associated device can be compensated for by increasing the duration of solution action, care is necessary as the toxicity of an agent usually increases with time (14). These results are in agreement with those of a previous study (22), which reported that root canal walls were cleaner, and the time required for satisfactory SL removal was shorter, for sonic activation of QMix than for conventional needle irrigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the EC group, in which QMix was used for 1 min, the results were similar to those in the group in which QMix was used for 3 min without activation. Although this suggests that the absence of an associated device can be compensated for by increasing the duration of solution action, care is necessary as the toxicity of an agent usually increases with time (14). These results are in agreement with those of a previous study (22), which reported that root canal walls were cleaner, and the time required for satisfactory SL removal was shorter, for sonic activation of QMix than for conventional needle irrigation.…”
Section: Discussionsupporting
confidence: 89%
“…It is important to point out, however, that agitation of root canal irrigants may increase apical extrusion in conjunction with factors such as root canal anatomy and the technique used. The safety of QMix is comparable to that of the most commonly used root canal irrigant, NaOCl (14). Thus, if the use of auxiliary devices to agitate QMix is performed with caution, apical extrusion of this solution is likely to be limited or nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkahtani et al reported that NaOCl solution has toxic effects on human bone marrow mesenchymal stem cells (MSCs) 70) . Martin et al also reported that high concentrations of NaOCl can drastically effect the survival and differentiation of stem cells of the apical papilla (SCAPs) and significantly reduce the expression of dentin sialophosphorprotein (DSPP) 71) .…”
Section: The Effect Of Dental Treatments and Materials On Angiogenesimentioning
confidence: 99%
“…Unlike NaOCl, QMix leads to cell death more slowly, without any cell lysis (124). Currently, there are no clinical studies investigating the efficacy of QMix as a final irrigant.…”
Section: Qmixmentioning
confidence: 99%